Integrating Digital Marketing and Local Wisdom to Enhance MSME Performance in North Sumatra - Risma Munte; Dermawan Peranginangin; Elfina Damanik; Dasmaika Haloho (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in regional economic growth and employment, yet many face limitations in both market expansion and long-term business sustainability. The rapid development of digital technology offers new opportunities through digital marketing, although many practices remain generic and overlook local cultural values. This study examines the effect of integrating digital marketing and local wisdom on MSME performance in North Sumatra Province using a quantitative approach with a survey design. Quantitative data were collected through questionnaires and analyzed using partial least squares structural equation modeling. The sample included MSMEs in locally rooted sectors such as culinary and handicrafts that actively use digital media. The results indicate that digital marketing and local wisdom both have positive and significant effects on enterprise performance, and that both factors together significantly explain the variance in sales growth, market reach, and business sustainability. This study contributes by proposing a culture-based digital marketing model for MSMEs and offers practical implications for entrepreneurs and policymakers to integrate digital capabilities with local cultural storytelling in the digital economy era.